Immunization to rituximab is more frequent in systemic autoimmune diseases than in rheumatoid arthritis: ofatumumab as alternative therapy. (9th October 2019) - Combier, Alice; Nocturne, Gaétane; Henry, Julien; Belkhir, Rakiba; Pavy, Stephan; Le Tiec, Clotilde; Descamps, Elise; Seror, Raphaele; Mariette, Xavier
Abstract: Objectives: The frequency and consequences of anti-drug antibodies to rituximab (RTX-ADA) are not well known in RA and even less in other systemic auto-immune diseases (sAID). We aimed to evaluate the frequency, consequences and predictive factors of RTX-ADA in RA and sAID. Methods: All patients presenting with RA or other sAID treated with RTX from 2012 to 2017 in our tertiary reference centre for sAID were retrospectively studied. Patients who were tested for RTX-ADA were identified. Results: One hundred and ninety-nine patients were treated with RTX (RA: 124, other sAID: 75). Among 62/199 (31.1%) tested for RTX-ADA, 14 were positive: 3/35 RA (8.6%) and 11/27 (40.7%) other sAID, ( P = 0.0047). Among the whole RTX-treated populations, the frequency of RTX-ADA was 2.4% and 14.7% ( P = 0.0026) in RA and sAID, respectively. Most of the immunized patients had infusion reactions to second or subsequent RTX cycles (11/14) and loss of efficacy (2/14). Predictive factors of immunization were sAID vs RA (78.6% vs 21.4%, P = 0.026, adjusted odds ratio (OR) = 5.35[1.43—54.75]) and African ethnicity (57.1% vs 4.2%, P < 0.001, adjusted OR = 9.25 [5.08—302.12]). Associated immunosuppressive therapy did not protect against immunization. Three patients with pSS immunized against RTX were treated with ofatumumab with complete remission of their disease. Conclusion: Immunization against RTX is more frequent in other sAID than in RA. Testing for RTX-ADA must be performed in patients with infusion reactions or loss of efficacy especially if they are of African origin. Immunized patients might be treated efficiently and safely with ofatumumab. This alternative should be further evaluated for sAID.